PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DAN KETERAMPILAN ANGGOTA PMR TENTANG PERTOLONGAN PERTAMA SINKOP DAN LUKA RINGAN DI SMA NEGERI 9 KTA BENGKULU - Feni Eka Dianty; Desi Susilawati; Mey Lisa Ginting (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2023)
The incidence of syncope in the world is estimated at around 12 million cases each year and the incidence of injuries according to research conducted in America is 20.4 cases. First aid is needed to deal with these cases of syncope and minor injuries. The purpose of this study was to determine the level of knowledge and skills of adolescent red cross members before and after health education and the effect of health education on the knowledge and skills of adolescent red cross members regarding first aid for syncope and minor injuries. This study uses a type of quantitative research with a quasi-experimental method with one group pre and post test. The sample in this study were 25 people with a total sampling technique. Data collection using questionnaires and observation sheets. The results of the study before being given health education showed knowledge about syncope in the sufficient category and skills in the less category while for minor injuries the level of knowledge was in the good category and skills in the less category. The results of the study after being given health education the level of knowledge and skills of syncope and minor injuries was in the good category. The conclusion of this study is the results of the Wilcoxon test, knowledge and skills pre and post syncope tests show that the p-value≤α, which means there is a significant difference, meaning that there is an influence of health education in providing first aid for syncope. However, the variable knowledge of pre and post minor injuries shows that the p-value> α, which means there is no significant difference, while the skills show that the p-value <α means that there is an effect of health education on first aid skills for minor injuries in SMA Country 9 Bengkulu.